The Wood Carvings of Two Traditional Timber Mosques in Kelantan and Terengganu. Issue 1 (March 2021) - Wahid, J; Abdullah, A; Saleh, B M Kamel; Awad, J
Abstract: Wood carving has a long history in Malaysia. It is greatly influenced by the rich landscape of tropical forest in the living environment of the locals. The motifs of the carving are primarily derived from the images of flora and fauna. It mimics the intricate nature of leaves and flowers of the plants. The craftsmen initially use the bas-relief design consisting also of animal imageries on the boat's sides or sometimes on the house components and even the dagger handle. However, with Islam's arrival in the early 15th century, due to its teachings, contributed to the ban of animal images on art form. While most of the carvings are done on wood, there is no ample evidence of records available due to time and tides of the decaying process of the artwork. Likewise, there is no extensive research and documentation produced by academics to record the traditional wood carving of the Malays. Although few collections had documented the contemporary Malay houses produced by local scholars, sadly, there was no recount on the importance of housing elements and the technique of construction neither on wood carving. Hence, this paper attempts to examine the influence and pattern of wood carving on traditional mosques in Kelantan and Terengganu. The research conducted case studies, to seek the signs of the features and elements of wood carving on the traditional mosque in Kelantan and Terengganu, disclosing the influence of patterns and motifs on the selected images of its architecture. A measured drawing technique commonly used in conservation works guided the research operation which comprised of hand-drawn sketches to capture the details, measurement of building components, as well as transferring the images using tracing paper, while the other methods in gathering the information extended to direct interviews and photography. Then, the data collected were analyzed to determine the differences of each carving patterns and motifs in the two mosques in Kelantan and Terengganu. The result of the research established the future records on the variety of motifs and patterns of the Malay wood carving. Subsequently, it further elaborates the extensive techniques of wood carvings system and records the patterns found at Kelantan and Terengganu's mosques for future inventory and recorded history.